2017
DOI: 10.1016/j.asoc.2017.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic modeling and visualization for bankruptcy prediction

Abstract: In accounting and finance domains, bankruptcy prediction is of great utility for all of the economic stakeholders. The challenge of accurate assessment of business failure prediction, specially under scenarios of financial crisis, is known to be complicated. Although there have been many successful studies on bankruptcy detection, seldom probabilistic approaches were carried out. In this paper we assume a probabilistic point-of-view by applying Gaussian processes (GP) in the context of bankruptcy prediction, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 44 publications
(45 reference statements)
2
43
0
2
Order By: Relevance
“…A summary of these models can be observed in Table 1. Altman (1968), Lennox (1999), Min and Lee (2005), Cho, Kim, and Bae (2009), Lee and Choi (2013), Barboza et al (2017), García, Marqués, Sánchez, and Ochoa-Domínguez (2017) Logit Basic Ohlson (1980), Lennox (1999), Min and Lee (2005), Cho et al (2009), Premachandra, Bhabra, and Sueyoshi (2009), Tseng and Hu (2010), Antunes et al (2017), Barboza et al (2017), García et al (2017) Squared interval logit Tseng and Hu (2010) Probit Basic Zmijewski (1984), Lennox (1999) However, problems are directly encountered regarding (i) the high volume of dimensions and (ii) heterogeneity. Nonparametric approaches that seek to analyze heterogeneous effects perform well in applications with small quantities of variables (Wager & Athey, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of these models can be observed in Table 1. Altman (1968), Lennox (1999), Min and Lee (2005), Cho, Kim, and Bae (2009), Lee and Choi (2013), Barboza et al (2017), García, Marqués, Sánchez, and Ochoa-Domínguez (2017) Logit Basic Ohlson (1980), Lennox (1999), Min and Lee (2005), Cho et al (2009), Premachandra, Bhabra, and Sueyoshi (2009), Tseng and Hu (2010), Antunes et al (2017), Barboza et al (2017), García et al (2017) Squared interval logit Tseng and Hu (2010) Probit Basic Zmijewski (1984), Lennox (1999) However, problems are directly encountered regarding (i) the high volume of dimensions and (ii) heterogeneity. Nonparametric approaches that seek to analyze heterogeneous effects perform well in applications with small quantities of variables (Wager & Athey, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, SVM presented the best results compared with the other models studied, presenting intermediate performance. Comparing the Gaussian model with SVM and the logit model, better predictions were found with the Gaussian process than with SVM and logit, as well as slightly higher accuracy of SVM compared to logit (Antunes, Ribeiro, & Pereira, 2017). Barboza, Kimura, and Altman (2017) compared various methodologies with ML and concluded that these present a substantial improvement in bankruptcy prediction, with around 10% more precision, especially when they include, besides the variables proposed by the Altman z score, some complementary financial indicators.…”
Section: Bankruptcy and MLmentioning
confidence: 99%
“…In [35], a probabilistic point-of-view by employing Gaussian processes (GP) was considered in the context of bankruptcy prediction, comparing it against LR and SVM. Based on real-world bankruptcy data, an in-depth analysis was implemented showing that, also a probabilistic interpretation, the GP can efficiently enhance the bankruptcy prediction performance with high accuracy when compared to the other techniques.…”
Section: ) Other Machine Learning Techniquesmentioning
confidence: 99%
“…Each individual method has advantages and disadvantages in predicting financial distress [24]. Therefore, more and more researchers have tried to employ individual methods as classifiers to construct ensemble models for financial distress prediction [25]. The main purpose is to improve predicting performance by taking full advantages of classifiers and in the same time minimizing their disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose is to improve predicting performance by taking full advantages of classifiers and in the same time minimizing their disadvantages. A lot of ensemble models have been proposed for financial distress prediction [25,26]. Recently, Alaka et al [27] investigated a systematic review of financial distress prediction models.…”
Section: Introductionmentioning
confidence: 99%